EVALUATION OF ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY OF GLYCYRRHIZA GLABRA ROOT EXTRACTS - BHUSAL, SHUSHIL; SHARMA, KHAGA RAJ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The present study was designed to investigate the phytochemical analysis, antioxidant potential, and antibacterial activities of the traditionally used medicinal plant Glycyrrhiza glabra. Methods: The plant secondary metabolites were extracted through cold percolation using methanol (MeOH) as a solvent. The MeOH extract was further fractionated in different solvents in increasing order of polarity. The antioxidant activity was evaluated by 2,2-diphenyl-1-picrylhydrazyl assay. The antibacterial activity was studied by agar well diffusion method. Results: The antioxidant potential IC50 was found 43.13, 104.83, and 200.11 μg/ml for ethyl acetate (EtOAc), MeOH, and chloroform (CHCl3) extracts, respectively. The EtOAc fraction showed the potent antioxidant with IC50 43.13 μg/ml compared to the standard ascorbic acid 58.76 μg/ml. The antimicrobial activity exhibited by MeOH extract against Bacillus subtilis (ATCC 6051) and Staphylococcus aureus (ATCC 6538P) zone of inhibition was 18 mm and 17 mm, for chloroform extracts 15 mm and 13 mm, and for EtOAc fraction 11 mm against Bacillus subtilis. The highest dilution that yielded no single bacteria colony on the nutrient agar plates for Bacillus subtilis and S. aureus of MeOH extract was found 0.39 mg/ml and 6.25 mg/ml, for chloroform extract 3.125 mg/ml and 6.25 mg/ml and EtOAc fraction against Bacillus subtilis was 12.50 mg/ml as minimum bactericidal concentration. Conclusion: The plant extracts showed potent antioxidant and antibacterial activity. The results support for using the G. glabra in bacterial infection which provides partial scientific validation for using the plant against bacterial infections.